Thin-film heat-sensitive elements on the basis of semimetals for electromagnetic radiation receivers - Mikhail A. Kik; Ilya A. Golokolenov; Aleksandr S. Sigov; Anatoly A. Shilyaev; Vitaly V. Zavyalov; Sergey S. Verbitsky; Aleksey N. Tselebrovsky (Российский технологический журнал, 2020)
The paper presents the generalized results of the authors’ work on the study of thin films of semimetals, which can be used in the development of universal electromagnetic radiation receivers. It is shown that thin-film materials based on semimetals have high thermal sensitivity, low intrinsic noise and an increased absorption coefficient of radiation in the millimeter region of the spectrum. Samples of bismuth films and bismuth–antimony films were obtained by vacuum thermal spraying. A study was made on the thermoelectric properties of bismuth–antimony thin films in the range from liquid helium temperature to room temperature in order to use these films as a bolometric type sensitive element in the range from infrared to radio frequency. A scheme and description of experimental installations for measuring current-voltage characteristics and determining the resistance of samples in the temperature range 1.4–400 K are presented. In the course of the study, the current-voltage characteristics and the temperature dependences of the resistance of film samples with a thickness of 80 and 20 nm were obtained. The characteristics of the manufactured prototype receiver were measured and used as a basis for estimating the possibility of developing bolometric-type receivers with increased NEP (Noise Equivalent Power). The NEP of the manufactured receivers at a frequency of 147 GHz was measured at room temperature and appeared to be ≈(0.3÷1)∙10–9 Hz1/2. This NEP value can be improved by cooling the receiver to liquid nitrogen or helium temperatures.